Management Policy on Employee Satisfaction (Case Study at Millennials Cafe Bangkalan) - Toha Mahsun; Agustin Pratiwi; Riha Fitria Ardelia; Iriani Ismail (Formosa Journal of Applied Sciences, 2023)
This research is a qualitative descriptive study. The population and samples taken were 13 employees. The tool used in this research is interviews. Primary data was obtained through asking questions to employees. Secondary data is obtained from written documents, such as journals which have data correlation with the research theme. The data analysis technique used is the triangulation test, namely source triangulation which consists of data reduction, data presentation and conclusions. The results of this research are assessed through various aspects of job satisfaction, such as salary level, nature of work, and work supervision and work environment. Therefore, companies cannot assess employee satisfaction based only on one aspect, but need to ensure employee satisfaction involves various factors, including salary. , nature of work, work supervision, and work environment.